Sustainable Consumption Harmonizes Life with Islamic Sharia - Giyan Wahyudha Putra (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
Sustainable consumption is an approach that prioritizes the wise use of resources to meet current needs without compromising the capabilities of future generations. In the context of Islamic law, this concept is in line with the principles of ethics, justice and responsibility towards the environment. This research aims to explore how sustainable consumption can be integrated with Islamic teachings, as well as its impact on people's lives. Islamic law encourages its followers to live simply, avoid waste, and respect natural resources as a trust from Allah. Through this approach, individuals and communities are invited to apply the principles of responsible consumption, such as choosing environmentally friendly products, supporting fair trade practices, and reducing negative impacts on the ecosystem. This study uses qualitative methods with in-depth literature analysis of Islamic texts and community practices that have implemented sustainable consumption. The results show that there is a close relationship between Islamic teachings and the principles of sustainable consumption, which can increase environmental awareness and create a more sustainable society. Thus, the implementation of sustainable consumption not only contributes to environmental welfare, but also strengthens spiritual and social values ​​in the daily lives of Muslims. It is hoped that this research can contribute to the development of policies that better support the integration of sustainable consumption and Islamic law. Keywords: Sustainable Consumption, Islamic Sharia, Environmental Ethics, Social Responsibility, Sustainability